La Rencontre à la Porte dorée. Image, texte et contexte - Réjane Gay-Canton (L'Atelier du CRH)
By analysing a series of illustrated German manuscripts between the last quarter of the xivth century and the second half of the xvth century, the essay shows that only very few images depicting the meeting of Anne and Joachim at the Golden Gate refer to the Immaculate Conception. Upon its inclusion in Heinrich von München’s Weltchronik and in the Historienbibel, Bruder Philipp’s Marienleben retains its maculist position. In the second text however, the image of the Meeting at the Golden Gate takes on a different meaning depending on the addition or suppression of a titulus mentioning the fertilizing kiss. After noting the effects of these changes to the image and emphasizing the image’s independence from both text and theology, the essay revisits the origins of the idea of the fertilizing kiss. It shows that this idea is neither found directly in the first literary texts mentioning Mary’s conception, the apocryphal Christian literature, nor is it a result of theological developments, but rather it indeed results from the combination of both these mediums and the image of the Meeting at the Golden Gate. The idea of the fertilizing kiss remains the particularity of the illitterati who found in it a means of circumventing the Augustinian theory of the transmission of original sin, by attributing to the future mother of God a conception free of all carnal concupiscence. Seen from this perspective, the image becomes the screen onto which the mental image is projected. It becomes laden with new meaning and interacts with the text, that it no longer illustrates but for which it now offers a parallel reading. Ultimately, it is only by placing it in its proper context that one can possibly determine, on a case-by-case basis, whether the image of the Meeting refers to the fertilizing kiss and thereby to the Immaculate Conception.